Digitalization of Trade as a Factor of Development of Export Potential of the Republic of Belarus - N. V. Yurova (Цифровая трансформация)
The purpose of the article is to show how the digitalization of trade can lead to the development of the export potential of the Republic of Belarus. The article discloses theoretical approaches to digitalization of trade as a combination of traditional and new digital models of interaction between buyer and seller. The author presents the volume, commodity and geographical structure of foreign trade of the Republic of Belarus, lists the priorities and identifies the main prospects for the development of exports using modern digital platforms and the emergence of new digital goods and services. The advantages of paperless trade and the need to implement the main provisions of National Strategy for Sustainable Socio-Economic Development of the Republic of Belarus are indicated. The author proposes the ways of development of the export potential of the Republic of Belarus witch based on an analysis of the processes of digital transformation of Belarusian trade.